PENGARUH TEKNIK KOMBINASI HIDROTERAPI RENDAM HANGAT DAN TERAPI RELAKSASI BENSON TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS MAEK KECAMATAN BUKIK BARISAN - Lisa Mustika Sari; Niche Ardila (LPPM UNIVERSITAS PERINTIS INDONESIA, 2015)
World Health Organization (WHO) in 2011, as much as 29% or 1.6 billion people worldwide suffer from hypertension. Hypertension prevalence in Indonesia has reached 25.8% of the total adult population. PHC Maek data obtained from medical records (MR) in the year 2014 the number of visits as many as 297 people. The purpose of this study was to determine the effect of combination technique hydrotherapy bath warm and benson relaxation therapy decrease blood pressurein patients hypertension in maek health center bukik barisan sub district lima puluh kota regency year 2015. This research has been conducted on June 22 until July 5, 2015 in Puskesmas Maek. This study uses Pre experiment with the design of one group pretest-posttest, then the data is processed by using the t test dependent. The results showed no significant effect of the combination of hydrotherapy techniques and warm soak benson relaxation therapy to decrease blood pressure in hypertensive patients in sub-district health centers Bukik maek row in 2015. Judging from the results of the analysis of paired samples T-test systolic blood pressure obtained with p value of 0.001 <0.05 and diastolic blood pressure with p value 0,001 <0,05. Recommendations result of this study is not only to treat hypertension using medical drugs but can also use warm soak hydrotherapy and relaxation therapy benson regularly as a companion treatment.